ENGLISH TEACHERS' PERCEPTIONS IN THE IMPLEMENTATION OF MERDEKA CURRICULUM FOR HIGH SCHOOLS IN BANGKINANG KOTA SUB-DISTRICT - Hariza, Dzikra; Eliwarti; Mahdum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the perceptions of English teachers towards the implementation of the Merdeka Curriculum for high schools in Bangkinang Kota Sub-District, Kampar. The study used a Sequential Explanatory Mixed Methods design with two stages, namely quantitative data collection and analysis through questionnaires and qualitative data deepening through semi-structured interviews. The research sample consisted of 17 English teachers at SMAN 1, SMAN 2, and SMKN 1 Bangkinang Kota who were selected through purposive sampling. The results of the study show that in general, teachers have a positive perception of the Independent Curriculum, especially the flexibility of teaching modules, the student-centered learning approach, and the Pancasila Student Profile Strengthening Project (P5). Teachers consider this curriculum to be able to increase students' creativity, independence, and character. However, a number of obstacles were found such as limited training in the preparation of teaching modules, inadequate infrastructure, and difficulties in integrating the P5 project into English learning. This study concludes that continuous support in the form of training, provision of facilities, and collaboration between teachers, schools, and education authorities is needed so that the Independent Curriculum can be implemented effectively and sustainably.